Das Geschlecht der Migration - Bildungsprozesse in Ungleichheitsverhältnissen - Diehm, Isabell; Messerschmidt, Astrid (Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft, 2013)
The authors offer discourse-critical analyses on the gender-related theme of migration in public discourse. They present methodological considerations for researching educational processes in the migration society and open up possibilities for action against discrimination and for self-determination. This is based on the following questions: How can gender reflecters contribute to the development of educational concepts that are directed against national-cultural unambiguities and come closer to the realities of globalised societies with their manifold affiliations? And how do the structural conditions of migration affect gender relations and educational opportunities?